The endocrine profile of subcutaneous and visceral adipose tissue of obese patients - Dolinková, M; Dostálová, I; Lacinová, Z; Michalský, D; Haluzíková, D; Mráz, M; Kasalický, M; Haluzík, M (Molecular and cellular endocrinology, 2008)
The aim of the present study was to evaluate the expression profile of genes potentially related to metabolic complications of obesity in the whole adipose tissue and isolated adipocytes from subcutaneous (SAT) and visceral adipose tissue (VAT) from 12 non-diabetic obese women and 12 lean women. Real-time polymerase chain reaction was used for expression analysis of 41 genes of interest and two housekeeping genes. We found increased expression of specific proinflammatory and adipogenic genes and reduced expression of specific lipogenic and insulin signaling pathway genes in obese relative to lean women with no preferable localization in SAT or VAT depot. The gene expression significantly differed between adipocytes and adipose tissue but both contributed to the proinflammatory profile in obesity. We conclude that both SAT and VAT exhibit alterations in the expression of specific genes possibly contributing to proinflammatory and insulin resistance state and consequently to metabolic complications of obesity.
Keywords: obezita; Humans; mikročipová analýza; lidé středního věku; Microarray Analysis; Intra-Abdominal Fat; Female; dospělí; lidé; Adipocytes; Adult; Subcutaneous Fat; tukové buňky; ženské pohlaví; nitrobřišní tuk; Middle Aged; stanovení celkové genové exprese; Obesity; Gene Expression Profiling; podkožní tuk